BUSINESS TRANSFORMATION IN THE CONDITIONS OF THE INFORMATION AND NETWORK ECONOMY (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines the features of the transformation of modern business in the conditions of the information and network economy and the new challenges and opportunities associated with this process in the field of economic activity. The features of such a transformation are analyzed and its impact on entrepreneurship and the economic system as a whole is determined. It has been proven that there is currently a transition from traditional business models to flexible, adaptive systems that are able to effectively respond to rapid and dynamic changes in market demand and market competition conditions. It was determined that the information and network economy creates conditions for the deep integration of technologies into all aspects of modern business processes. The impact of digital technologies on the functional interaction between business entities in the process of economic activity is considered. It has been proven that network structures make it possible to form new models of economic cooperation by combining various industries and individual enterprises into large complex ecosystems, which opens up wide opportunities for the creation of new innovative products and services, as well as for the development of new markets. It was determined that the challenges facing modern enterprises in the conditions of the information and network economy consist in changing consumer requests, increasing the impact of cyber threats on business processes, as well as forming an objective need for enterprises to constantly update technologies in order to properly adapt to changing business conditions - environments. The specifics of the response of modern business to the challenges of the information and network economy, which can provide enterprises with the appropriate level of competitiveness and provide conditions for their sustainable development, are highlighted. It has been proven that innovations in management strategies, the use of the latest digital and information technologies, as well as the active participation of business in network relations become key components of successful business transformation in new economic conditions. It was determined that the information and network economy, in which the importance of data exchange and the use of digital technologies for optimizing business processes is growing, forms new paradigms in management and entrepreneurship. The role of artificial intelligence, the Internet of Things and blockchain technologies in the formation of modern effective business models is considered. It was determined that the development of digital tools contributes not only to automation, but also to rethinking the essence of resource management strategies, interaction with customers and the creation of fundamentally new innovative products.
Keywords: business transformation, information and network economy, innovation, digital transformation, strategic management.